Biomechanical characterization dismount from balance beam on the basis of the analysis of key elements of sports equipment - Potop, V.A.; Rafal, G.; Boloban, V.N.; Otsupok, A.P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose. Biomechanical analysis of sports performance technology with balance beam dismount. Material, methods. The study involved six young gymnasts aged 12 - 14 years old - the reserve team of Romania. Results. Identified nodal elements of sports equipment dismount from balance beam type flip off rondat and rondat - coup ago somersaults with twists caved at 360°, 540°, 720° and 900°. In the preparatory phase of the motor action performed dismount isolated and studied central element of sports equipment - starting posture of the body in the phase of the main motor action - animation body posture in the final phase of motor actions - the final posture of the body - Sustainable landing. Conclusions. The method of video - computer research dismount from balance beam type flip off rondat and rondat - coup ago, in conjunction with the method of postural orientation movements allow you to perform a detailed biomechanical analysis of the key elements of sports equipment, to develop advanced training programs.